MITHRAS AND THE ZODIAC - Luca Amendola (Journal of Ancient History and Archaeology)
The Roman cult of Mithras has been the object of many controversies, for instance the question of the origin, the mythology, and the role of astronomical-astrological concepts. In this article we focus on another controversial point, the existence and content of a doctrine of salvation. We review systematically the literary, epigraphic, architectural, and iconographic evidence of salvation in Mithraism. We find that the evidence supports the existence of a doctrine that included a soul journey towards the solstices, along the lines of a famous passage in Porphyry's De antro nympharum.